AN EVALUATION ON CHARACTERISTIC DIATOMS OF ALKALINE LAKE HAZAR (TURKEY) - Sonmez, Feray; Kocer, Mehmet Ali Turan; Alp, Mehmet Tahir; Sen, Bulent (Parlar Scientific Publications (P S P), 2018)
In this study, data on occurrence and abundance of diatoms reported by the five studies carried out between 1991 and 2005 in the alkaline Lake Hazar were mined using univariate and multivariate statistics. A total of 157 diatom taxa have been reported in phytoplankton, epilithon and epipelon. Cymbella affinis, Epithemia turgida and Gomphonema olivaceum were the most common taxa on the basis of relative frequency both in phytoplankton and benthic algal associations. Hierarchical cluster analysis clearly grouped the taxa into two major clusters, discriminating common and dominant species than rare and scarce taxa. Principal component analysis, revealing the spatial and temporal variation of dominant and subdominant taxa, suggested seasonality of diatoms in different habitats of the lake. Most of the diatoms recorded in Lake Hazar that are typical alkalibiontic and oligotraphent species occurred rarely or scarcely in phytoplankton and periphyton. On the other hand, reaching to high abundances of meso-eutraphent species indicated a response to increased nutrients in the lake.
Keywords: Diatoms; alkaline lake; oligotrophic; indicator species; phytoplankton; periphyton